Absorption, distribution, metabolism and excretion of telmesteine, a mucolitic agent, in rat - Lee, J; Son, J; Rhee, SW; Kim, DH (TAYLOR & FRANCIS LTD, 2003)
1. The metabolism and disposition of telmesteine, a muco-active agent, have been investigated following single oral or intravenous administration of C-14-telmesteine in the Sprague-Dawley rat. 2. C-14-telmesteine was rapidly absorbed after oral dosing (20 and 50 mg kg -1 ) with an oral bioavailability of >90% both in male and female rats. The C max and area under the curve of the radioactivity in plasma increased proportionally to the administered dose and those values in female rats were 30% higher than in male rats. 3. Telmesteine was distributed over all organs except for brain and the tissue/plasma ratio of the radioactivity 30 min after dosing was relatively low with a range of 0.1-0.8 except for excretory organs. 4. Excretion of the radioactivity was 86% of the dose in the urine and 0.6% in the faeces up to 7 days after oral administration. Biliary excretion of the radioactivity in bile duct-cannulated rats was about 3% for the first 24 h. The unchanged compound mainly accounted for the radioactivity in the urine and plasma. 5. Telmesteine was hardly metabolized in microsomal incubations. A glucuronide conjugate was detected in the urine and bile, but the amount of glucuronide was less than 6% of excreted radioactivity.
Keywords: ESCHERICHIA-COLI